The effects of physical exercise on cognitive function in adolescents: a systematic review and meta-analysis - Liu, Longyan; Xin, Xianyang; Zhang, Ying (Frontiers in Psychology, 2025)
ObjectivePhysical exercise holds promise for improving cognitive function development in adolescents. However, current research evidence remains inconsistent. This systematic review and meta-analysis primarily aimed to determine the overall impact of physical exercise interventions on adolescent cognitive function. It also extended to explore effects on specific cognitive domains (such as executive function, attention, working memory, cognitive flexibility, and inhibitory control) and to examine potential differences across various exercise types.MethodA comprehensive search was conducted across multiple databases, including Web of Science, Embase, PubMed, the Cochrane Central Register of Controlled Trials, and CBM, to identify randomized controlled trials (RCTs) investigating the effects of physical exercise on cognitive function in adolescents. The search covered studies published from the inception of these databases through November 30, 2024. This protocol is registered with PROSPERO (CRD42024605962). A preliminary search of the databases and referenced citations identified 2,910 records. Standardized mean differences (SMD) and 90% confidence intervals (CI) were employed to calculate and aggregate the effect sizes for outcome measurement.ResultsA total of 21 studies were included in this meta-analysis. Considering that cognitive function comprises multiple domains and that different studies use diverse outcome measures to evaluate adolescent cognitive function, a subgroup analysis was conducted. The studies were grouped into categories such as executive function, attention, working memory, cognitive flexibility, and inhibitory control to better capture changes in adolescent cognitive abilities. The findings demonstrate that physical exercise interventions lead to significant improvements in cognitive function among adolescents when compared to the control group. Notably, enhancements were observed in executive function (SMD = 0.21, 95% CI: 0.06 to 0.37), attention (SMD = 0.56, 95% CI: 0.34 to 0.78), cognitive flexibility (SMD = 0.42, 95% CI: 0.26 to 0.58), inhibitory control (SMD = 0.58, 95% CI: 0.22 to 0.94), and working memory (SMD = 0.54, 95% CI: 0.16 to 0.91). The subgroup analysis revealed that aerobic exercise had the greatest impact on cognitive function (SMD = 0.53, 95% CI: 0.32 to 0.73), particularly in areas such as executive function and attention, compared to other exercise modalities. This suggests that aerobic exercise may be particularly effective in enhancing adolescent cognitive abilities.ConclusionPhysical exercise has been shown to enhance cognitive function in adolescents. Based on the findings of this Meta-analysis, it is recommended that adolescents participate in at least moderate-intensity physical activities, such as aerobic exercise or resistance training, to promote cognitive development.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024605962; Identifier: CRD42024605962.